Pengaruh Ulasan Online Terhadap Keputusan Pembelian Produk pada Platform Shopee - Mutmainah Mutmainah (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of digital technology has changed consumer behavior patterns, including the process of making online purchasing decisions. One factor influencing these decisions is online reviews on e-commerce platforms. Shopee, as one of the largest e-commerce platforms in Indonesia, provides reviews containing information about product quality and previous consumer experiences, which can help potential buyers in considering their choices. This study aims to analyze the influence of online reviews on purchasing decisions for fashion products on Shopee. The research method used a quantitative approach with a survey of 100 respondents, namely Shopee users who had made purchases and read online reviews before making transactions. Data were collected through an online questionnaire using Google Forms, then processed using SPSS version 25. Data analysis included validity tests, reliability tests, descriptive statistics, and simple linear regression. The results showed that online reviews had a positive and significant effect on purchasing decisions. The R-squared value of 0.745 indicates that 74.5% of the variation in consumer purchasing decisions can be explained by online reviews, while the remainder is influenced by other factors. These findings confirm that online consumer reviews play a significant role in increasing trust and encouraging product purchases. Therefore, sellers on Shopee are advised to maintain product quality, provide accurate information, and encourage positive consumer reviews. This strategy can help improve store image, build consumer trust, and strengthen product competitiveness in the increasingly competitive e-commerce market.